برنامج إرشادي لتنمية الثقة بالنفس لدى المكفوفين - الداوودي، لانا نجم الدين; أبو فخر، غسان عبدالحي (جامعة عدن - كليات التربية, 2012)
أصبح الاهتمام بالأطفال غير العاديين من المؤشرات الحضارية لدول العالم وقـد اخذت المجتمعات تخطو خطوات سريعة في هذا الميدان العلمي الإنسـاني كمـا أخـذت بعض الدول النامية تتسابق في تقديم الخدمات الاجتماعية والتربوية والنفسية والصحية لفئات المعاقين وفي مقدمتها فاقدي البصر(راشد ١٩٩٧ص٣). \ ان رعاية الأطفال المعاقين بشكل عام وفاقدي البصر بشـكل خـاص يجـب ان لا ينظر اليها باعتبارها منحة تقدم لهؤلاء بل هي حق طبيعي يكتسبه الطفل بحكم كونـه انسانا وجد في هذا المجتمع وقد اكدت الشرائع الدينية والوضعية حقهـم فـي العـيش بسعادة واهتمام واعتمدت الجمعية العامة للأمم المتحدة هذا المفهوم في دورتها السابعة و الثلاثين بقرار ٣٧\\٥٢في كانون الاول ١٩٨٢. ومما هو جـدير بالـذكر ان النمـو البصري للفرد يعتبر مظهرا أساسيا من مظاهر النمو الجسمي إذ يبـدأ منـذ الـولادة ويتطور تدريجيا إلى ان يصبح نسبة اكتساب الخبرات والتعلم من خلالـ ه ٧٥الـى٨٠%للفرد. ان مظاهر الإعاقة البصرية هذه تقودنا إلى عدم إهمال مضاعفات الخلل الأقل وضوحا لدى المعاقين ولكنها من حيث النتائج اشد خطورة على النمـو النفسـي العـامل لطفل. فعندما نتصور ان أهمية البصر بالنسبة للنمـو العـاطفي والفكـري والنفسـي و الاجتماعي فإننا ندرك ان فاقد البصر يعتمد على غيره في ترجمة تلك المشاعر فهـو ينقصه الحافز الحيوي للنمو واستكشاف البيئة المحيط به و عنـد ذلـك تتجـه نمـو شخصيته إلى الانحراف بإحساسه بأنه يختلف عن الآخرين ولافتقـاره المسـتمر إلـى الشعور بالثقة بالنفس التي يكتسبه الطفل العادي من خلال انجازاته المادية وتقبل ثنـاء الآخرين لذلك يتخذ بعض المعاقين بصريا ملاذا في عجزهم فـي التهـرب مـن القيـام بمهمات لا يستطيعون انجازها فعملية الثقة بالنفس أو تنميتها تحتـاج إلـى اسـتخدام برامج إرشادية لكي يحدث هذا النمو و التغير إذ ان هناك صلة بين الإرشـاد وعمليـة الثقة بالنفس وهذه تظهر من خلال التدريب الإرشادي لأنه يـزود الفـرد بالمعلومـات والخبرات من خلال قنوات متنوعة لتجعله قادرا على مواجهة الظروف الصـعبة التـي يعاني منها النفسية أو الاجتماعية أو الصحية . فلإرشاد عنصر أساسي في عملية زيادة الثقة بالنفس وفهم الحياة. Attention of the unordinary children has become an indicator of civilized societies in the world and has taken communities towards a quick steps in this scientific field of human and as we see some developing countries are now racing to provide social, educational, psychological and health services for the categories of disabled persons, particularly blind people (Rashid ١٩٩٧, p. ٣). \ That care for children with disabilities in general and the blind in particular, should not be considered as a grant to those we’ve mentioned, it is a natural right derived by a child by virtue of being a human being found in this community. The religious laws and the situation of them have confirmed their right to live happily and to gain the interest of the General Assembly adopted by the United Nations in the seventy third course - resolution ٣٧ \\ ٥٢ December ١٩٨٢. It is worth mentioning, that the growth of optical individual Iatbermzara is a key aspect of physical growth as it begins at birth and develops gradually to become the percentage of gain experience and learn about ٧٥ to ٨٠٪ of an individual. The manifestations of visual disability, lead us not to neglect consequences of the flaw the less obvious with the disabled ,but in terms of results, the more serious the psychological development of the child. When you think about the importance of vision for the growth of emotional, intellectual, psychological and social aspects, we realize that the blind rely on others to translate those feelings he lacks, and we see that the motivation is vital for growth and explore the environment around him and when you are moving the growth of his personality to deviation its sense of being different from others, and lack of continuing to feel self-confidence which is normally acquired by the children through the material achievements of physical, accepting the praise of others. Therefore, some of them would take some visually impaired refuge in their inability to escape from doing missions they can not accomplish. The self-confidence or their development would need an extension programs to obtain such a growth and change because there is a link between extension and the process of self-confidence and this shows through extension training because it provides the individual with information and experiences through various channels to make him able to confront the difficult conditions he suffered by the psychological, social or health.The guidance is a key element in the process of increasing confidence self-esteem and understanding of life.
650036
Keywords: الذكور -- الثقة بالنفس -- الطلاب المعوقون -- الإعاقة البصرية -- رعاية الأطفال -- الفروق الفردية -- الإناث -- التحليل النفسي -- معهد النور للعوق البصري -- بغداد